Novel route for rapid biosynthesis of copper nanoparticles using aqueous extract of Calotropis procera L. latex and their cytotoxicity on tumor cells - Harne, Shrikant; Sharma, Ashwinikumar; Dhaygude, Mayur; Joglekar, Shriram; Kodam, Kisan M.; Hudlikar, Manish (Colloids and Surfaces B-Biointerfaces, 2012)
This paper accounts for novel, low-cost, eco-friendly route for rapid biosynthesis of copper nanoparticles. Cysteine proteases present in the latex of Calotropis procera L. were used to fabricate copper nanoparticles from copper acetate. Copper nanoparticles were initially characterized by transmission electron microscopy (TEM) and X-ray diffraction technique (XRD). Transmission electron microscopy (TEM) was used to estimate the size and shape of nanoparticles. The average size of copper nanoparticles was found to be 15 +/- 1.7 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of copper. Fourier transform infrared spectroscopy (FTIR) was performed to confirm capping behavior of the latex proteins that contributed to long term stability of copper nanoparticles (6 months) in aqueous medium. Copper nanoparticles synthesized by above method were monodisperse type. Cytotoxicity studies of latex stabilized copper nanoparticles were carried out on HeLa, A549 and BHK21 cell lines by MTT dye conversion assay. HeLa, A549 and BHK21 cells showed excellent viability even at 120 mu M concentration of copper nanoparticles. This shows that copper nanoparticles synthesized by above method hold excellent biocompatibility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biocompatible; Copper nanoparticles; FTIR; Latex; Tumor cells; X-ray diffraction technique (XRD)

Mechanistic insights into enzymatic catalysis by trehalase from the insect gut endosymbiont Enterobacter cloacae - Adhav, Anmol; Harne, Shrikant; Bhide, Amey; Giri, Ashok; Gayathri, Pananghat; Joshi, Rakesh (FEBS Journal, 2019)
Energy metabolism in the diamondback moth Plutella xylostella is facilitated by trehalase, an enzyme which assists in trehalose hydrolysis, from the predominant gut bacterium Enterobacter cloacae. We report the biochemical and structural characterization of recombinant trehalase from E. cloacae (Px_EclTre). Px_EclTre showed K-M of 1.47 (+/- 0.05) mm, k(cat) of 6254.72 min(-1) and V-max 0.2 (+/- 0.002) mm center dot min(-1) at 55 degrees C and acidic pH. Crystal structures of Px_EclTre were determined in the ligand-free form and bound to the inhibitor Validoxylamine A. The crystal structure of the ligand-free form, unavailable until now for any other bacterial trehalases, enabled us to delineate the conformational changes accompanying ligand binding in trehalases. Multiple salt bridges were identified that potentially facilitated closure of a hood over the substrate-binding site. A cluster of five tryptophans lined the -1 substrate-binding subsite, interacted with crucial active site residues and contributed to both trehalase activity and stability. The importance of these residues in enzyme activity was further validated by mutagenesis studies. Many of these identified residues form part of signature motifs and other conserved sequences in trehalases. The structure analysis thus led to the assignment of the functional role to these conserved residues. This information can be further explored for the design of effective inhibitors against trehalases.
Keywords: Enterobacter cloacae; Plutella xylostella; structural analysis; trehalase; validoxylamine A